Education about healthy aging to elderly in st.Vincentius a Paulo's church Surabaya - Lilyana, Maria Theresia Arie; Julian, Alvin (Universitas katolik Musi Charitas, 2024)
Elderly are individuls who are more than 60 years age. Increasing age have an impact to decreased physical functional and susceptible to have several chronic disease as a form of geriatric syndrome in elderly. Aim of this activity is to improve elderly awareness about being healthy aging who are carried out through health education and filling out elderly vulnerability questionaire. The results of this activity can determine further activity that can be held in this elderly community of st. Vincentius a Paulo Surabaya church. The results of this activity showed 29 elderly (58%) from 50 participants have a symptom of fatigue as a result filling out elderlyy vulnerability questionaire. Fatigue in elderly can be caused by chronic illnes or sleep disorder due to various causes. Conclusion: based on the screening about elderly vulnerability, fatigue is majority experience for elderly.